If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = 5(x + 10) Reorder the terms: 3(4 + x) = 5(x + 10) (4 * 3 + x * 3) = 5(x + 10) (12 + 3x) = 5(x + 10) Reorder the terms: 12 + 3x = 5(10 + x) 12 + 3x = (10 * 5 + x * 5) 12 + 3x = (50 + 5x) Solving 12 + 3x = 50 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 12 + 3x + -5x = 50 + 5x + -5x Combine like terms: 3x + -5x = -2x 12 + -2x = 50 + 5x + -5x Combine like terms: 5x + -5x = 0 12 + -2x = 50 + 0 12 + -2x = 50 Add '-12' to each side of the equation. 12 + -12 + -2x = 50 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 50 + -12 -2x = 50 + -12 Combine like terms: 50 + -12 = 38 -2x = 38 Divide each side by '-2'. x = -19 Simplifying x = -19
| -6(z+8)-(8-4z)=-3z | | 6=y+13 | | 2x(2)-3x-1=0 | | 8+14b+3b^2=0 | | -6(z+8)-(8-4z)=-32 | | (x+7)^2/3=9 | | -2(x-2)=6x | | a=(5*2-2+4)/10 | | x+(x-1)+(x-2)=108 | | -6(3x+9)=54 | | (2x-5)2(4x+7)=2 | | -210=-5(-6p-6) | | 7(7+x)=84 | | 257.5x=60714.67 | | 12x^2+25y=300 | | a=4(7*7)+7(4*4) | | 5(y+3)-2(4y-10)=14 | | 257.5x=63276.07 | | (2x-5)3(4x+7)=2 | | 84=3(5x-7) | | 9(x-5)-5(x-2)=-2x | | 7x+34=11x-14 | | 257.5x=73996 | | 6z-0.6=7z | | a=3(7*7-4) | | (7w+8)/3+(w+8)/2=18 | | 8-7x=125 | | (3/7)+(2/3)+(1/2) | | 257.5x=53599.67 | | 257.5x=124749.67 | | (1/3)*(1/4) | | 3/4(-8x+12)=6 |